Swift and saddled ebook - Sage, Lyla (Rebel Blue Ranch, 2024)
NATIONAL BESTSELLER • She’s the city girl who refuses to be saddled with a man. He’s the cowboy who wants her anyway. From the author of the BookTok sensation Done and Dusted comes the next book in the Rebel Blue Ranch series, a small town romance featuring opposites attract and forced proximity. The last thing Ada Hart needs is a man to take care of her. Not anymore. After failing out of her interior design program and the disaster that was her short-lived marriage, Ada clawed her way up from her rock bottom. Now, the only person she trusts is herself, and that has gotten her further than ever before. She has her own business, and one of the largest ranches in Wyoming just hired her for the most important project of her career. When Ada arrives in Meadowlark, she finds herself in a dive bar where she can’t seem to shake the eyes of a handsome cowboy. When she leads him to the back of the bar, he leaves her with a kiss that most people can only fantasize about. She almost regrets that she’ll never see him again . . . except it turns out he’s her new boss. Weston Ryder is a happy guy. Even happier now that the mystery woman from the bar is the interior designer for his dream project on his family’s ranch. He feels like he hit the jackpot. It’s too bad she wants absolutely nothing to do with him outside of work. Ada is convinced the pull she feels toward Wes will go away, but Wes can’t stop thinking about her. Even though walls are coming down around Rebel Blue, Ada’s walls are firmly in place. Can they make it through this project without giving in? Or will they both put their dreams on the line for a chance at love?